The Role Of Digital Service Quality and Perceived Ease Of Use in The Adoption of Digital Wealth Management Among Millennial Farmers - Philipus, Cyndrika Rany; Tindi, Ricardo Gianluigi; Sintaro, Sanriomi (Jurnal Agroekoteknologi Terapan (JAT), 2026)
This study examines the roles of digital service quality and perceived ease of use in shaping adoption intention toward digital wealth management among millennial farmers. Drawing on a service marketing perspective and technology acceptance logic, the study also positions trust as a key mechanism that links service perceptions to adoption intention. A structured questionnaire was administered to 236 millennial farmers (aged 20–39), and the proposed model was analyzed using partial least squares structural equation modeling (PLS-SEM) with bootstrapping. The descriptive results indicate that perceived ease of use is generally high, reflecting respondents’ familiarity with smartphones, while perceptions of service quality and trust vary more substantially. The structural model shows that digital service quality strongly predicts trust (β = 0.991, p < 0.001) and that trust strongly predicts adoption intention (β = 0.810, p < 0.001). Digital service quality also has a small but significant direct effect on intention (β = 0.183, p = 0.012), indicating partial mediation. The indirect effect of digital service quality on intention through trust is large and significant (β = 0.803, p < 0.001), confirming that trust transmits most of the impact of service quality. Perceived ease of use shows statistically significant but small effects on trust and intention, suggesting usability functions primarily as a baseline enabler for digitally capable millennials. The model explains substantial variance in trust (R² = 0.979) and intention (R² = 0.981). Discriminant validity diagnostics indicate strong overlap among service quality, trust, and intention, suggesting that respondents may form a holistic evaluation of the platform; this limitation should be addressed through construct refinement in future research. Practically, the findings imply that increasing digital wealth management adoption in agricultural communities should prioritize trust-building service quality cues, including reliability, transparency, security assurance, and responsive support.